2016
DOI: 10.1097/md.0000000000004499
|View full text |Cite
|
Sign up to set email alerts
|

Decreased retinal nerve fiber layer thickness in patients with obstructive sleep apnea syndrome

Abstract: Objective:To investigate the changes of retinal nerve fiber layer (RNFL) thickness in obstructive sleep apnea syndrome (OSAS) patients.Methods:Relevant studies were selected from 3 major literature databases (PubMed, Cochrane Library, and EMBASE) without language restriction. Main inclusion criteria is that a case-control study in which RNFL thickness was measured by a commercial available optical coherence tomography (OCT) in OSAS patients. Meta-analysis was performed using STATA 12.0 software. Efficacy estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Several similar studies regarding RNFL thickness and OSA severity were later conducted, and a meta-analysis by Yu et al [37] showed that both moderate and severe OSA were associated with a significant decrease in average, superior, inferior, and nasal RNFL thickness on OCT [37]. Other meta-analysis studies have also provided similar results [38][39][40][41]. More recently, Liguori et al [30] demonstrated that patients with severe OSA exhibited a significantly more delayed latency and significantly lower amplitude of P100 waves on their visual evoked potential than the controls; however, electroretinography results did not differ significantly between the patients with OSA and controls [30].…”
Section: Discussionmentioning
confidence: 83%
“…Several similar studies regarding RNFL thickness and OSA severity were later conducted, and a meta-analysis by Yu et al [37] showed that both moderate and severe OSA were associated with a significant decrease in average, superior, inferior, and nasal RNFL thickness on OCT [37]. Other meta-analysis studies have also provided similar results [38][39][40][41]. More recently, Liguori et al [30] demonstrated that patients with severe OSA exhibited a significantly more delayed latency and significantly lower amplitude of P100 waves on their visual evoked potential than the controls; however, electroretinography results did not differ significantly between the patients with OSA and controls [30].…”
Section: Discussionmentioning
confidence: 83%
“…79 Previous papers have reported a strong link between OSA and optic nerve disorders. 7,[19][20][21][80][81][82][83][84] Studies of electrophysiology and RNFL thickness have reported conflicting findings in OSA patients, some showed significant reduction of the RNFL thickness, 9,19,21,71 pattern electroretinogram (PERG), 82,84 and visual evoked potential (VEP), 83,84 while others found no decrease [85][86][87] or alterations of ERG. 83 Our results did not show any reduction of RNFL thickness or VF in the OSA group, in agreement with previous studies by Salzgeber et al, 87 Ferrandez et al, 85,86 and Yu et al, 88 which did not find significant thinning of the RGC layer or macular thickness in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Studies with more than 6 stars were considered to be high quality studies. [ 28 , 29 ] Two authors performed the assessment independently and any disagreement was resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%